Från normativ hållning till politisk korrekthet? SAOL och normen under ett drygt sekel - Nikula, Kristina (Nordiske Studier i Leksikografi, 2010)
The aim of this article is to investigate if and how the concept of norm is discussed in Svenska Akademiens ordlista (Swedish Academy Glossary). This dictionary is also analysed as to its political correctness, because it was accused by some critics of being too politically correct after its publication in 2006. Using the principles of critical discourse analysis the investigation starts with the seventh edition (1900) and ends with the thirteenth (2006).